From monosensory to multisensory: how forests transform people’s understanding of landscape - Savela, Timo (Informa UK Limited, 2025)
This essay assesses how forests change how people experience the world. It demonstrates how they alter people’s encounters with landscape by preventing them from distancing themselves from and maintaining a sense of control over their surroundings. It examines how, much like art and darkness, forests deprivilege vision and privilege other human senses, which breathes life back to the surrounding landscape. The essay also acknowledges how forests and darkness are mutually reinforcing in this regard, and thus capable of drastically transforming people’s understanding of landscape and providing an escape from their semiotic enslavement through landscape.